Konsep Kesejahteraan Sosial Dalam Perspektif Ekonomi Pancasila Dan Ekonomi Islam - Kurnia Rusmiyati; Abu Syhabudin; Anggi Prayitno; Dea Puspita (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2026)
This study aims to examine and compare the concept of social welfare from the perspectives of Pancasila Economics and Islamic Economics. Amidst the dominance of the global capitalist economic system, Indonesia has a unique philosophical foundation, namely Pancasila Economics, while as a country with the largest Muslim population, the principles of Islamic Economics also have a significant influence. The method used in this study is library research with a descriptive comparative approach. The results of the study show that Pancasila Economics views social welfare as the embodiment of social justice for all Indonesian people, achieved through the principles of kinship, a people's economy, and the active role of the state in managing strategic resources in accordance with Article 33 of the 1945 Constitution. On the other hand, Islamic economics views welfare (falah) as the achievement of worldly and spiritual happiness based on Maqashid Syariah (protection of religion, soul, mind, offspring, and property) through instruments of wealth redistribution such as zakat, infaq, alms, and waqf. These two perspectives have a strong common ground in the principles of humanity, rejection of exploitation, and priority on equitable distribution of wealth to protect vulnerable groups. The fundamental difference lies in the source of authority: Pancasila Economics is based on national consensus and state ideology, while Islamic Economics is based on divine revelation. A synthesis of these two concepts is expected to become a solid foundation in the formulation of public policy to create a more inclusive and equitable social security system in Indonesia in the future.